A study on blockchain technology - S. G. Aruna Sri, P; Lalitha Bhaskari, D (International Journal of Engineering and Technology, 2018)
Blockchain is a one of emerging technology for decentralized and sharing of transactional data across a large peer to peer network, where non-trusting members can interact with each other without an intermediary, in a verifiable manner. In this paper, we review the basics of Blockchain, its applications, types, and working of Blockchain. Behind this innovative technique, the security, privacy issues and Con-sensus mechanisms of this technology are also important and are a matter of concern. The problems associated with Blockchain technol-ogy are also discussed in this paper.Â Â